How do you find the roots, real and imaginary, of #y=-5x^2 + 17x +12(x/2-1)^2 # using the quadratic formula?

Answer 1

#x=4#

or
#x=(-3)/2#

#-5x^2+17x+12(x/2-1)^2=0#
First we simplify the equation to bring it to the standard form. Therefore we need to simplify the third term of the equation using #(a-b)^2=a^2+b^2-2ab#
#-5x^2+17x+12((x/2)^2+1^2-2*x/2*1)=0#
#-5x^2+17x+12(x^2/4+1-x)=0#
#-5x^2+17x+(12x^2)/4+12-12x=0#
#-5x^2+17x+3x^2+12-12x=0#
#-2x^2+5x+12=0#
#2x^2-5x-12=0#
Here #a=2 , b=(-5) , c=(-12)#

This is the standard form of the equation. Now we can simply use the quadratic formula to find the roots of this equation.

#x=(-b+-sqrt(b^2-4ac))/(2a)#
#x=(5+-sqrt(25+96))/4#
#x=(5+-11)/4#
#x=(5+11)/4 , (5-11)/4#
#x=4# and #x=(-3)/2#
The Delta (#sqrt(b^2-4ac)#) of the equation was greater than zero therefore the roots are real and distinct. If the Delta was equal to zero, the roots would've been real and equal. If the Delta was less than zero the roots would've been imaginary and imaginary roots always come in pairs.
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the roots of the quadratic equation ( y = -5x^2 + 17x + 12(\frac{x}{2}-1)^2 ) using the quadratic formula, follow these steps:

  1. Rewrite the equation in standard form: ( y = ax^2 + bx + c ). ( y = -5x^2 + 17x + 12(\frac{x}{2}-1)^2 ) ( y = -5x^2 + 17x + 12(\frac{x^2}{4} - x + 1) ) ( y = -5x^2 + 17x + 3x^2 - 24x + 12 ) ( y = -2x^2 - 7x + 12 )

  2. Identify ( a ), ( b ), and ( c ) in the equation: ( ax^2 + bx + c ). ( a = -2 ) ( b = -7 ) ( c = 12 )

  3. Substitute the values of ( a ), ( b ), and ( c ) into the quadratic formula: ( x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} ). ( x = \frac{{-(-7) \pm \sqrt{{(-7)^2 - 4(-2)(12)}}}}{{2(-2)}} ) ( x = \frac{{7 \pm \sqrt{{49 + 96}}}}{{-4}} ) ( x = \frac{{7 \pm \sqrt{{145}}}}{{-4}} )

  4. Calculate the discriminant: ( b^2 - 4ac ). ( b^2 - 4ac = (-7)^2 - 4(-2)(12) ) ( b^2 - 4ac = 49 + 96 ) ( b^2 - 4ac = 145 )

  5. Evaluate the square root of the discriminant: ( \sqrt{{145}} ).

  6. Substitute the values of the discriminant and coefficients into the quadratic formula to find the roots. ( x = \frac{{7 \pm \sqrt{{145}}}}{{-4}} )

  7. Simplify the roots if possible.

Therefore, the roots of the equation ( y = -5x^2 + 17x + 12(\frac{x}{2}-1)^2 ) are given by: ( x = \frac{{7 + \sqrt{{145}}}}{{-4}} ) and ( x = \frac{{7 - \sqrt{{145}}}}{{-4}} )

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7